Phosporus Sufficiency for Growth and Production of Soybean under Saturated Soil Culture in Mineral and Peaty Soils: Kecukupan Hara Fosfor pada Pertumbuhan dan Produksi Kedelai dengan Budidaya Jenuh Air di Tanah Mineral dan Bergambut - Bachtiar, Bachtiar; Ghulamahdi, Munif; Melati, Maya; Guntoro, Dwi; Sutandi, Atang (Jurnal Ilmu Tanah dan Lingkungan, 2016)
The research objective is to determine the dosage and frequency of given of P fertilizer on soybean varieties in soil mineral and peaty mineral under saturated soil culture in tidal land. The research was conducted in mineral and peaty mineral soil of tidal area types B and C in the District of Tanjung Lago, Banyuasin Regency, Province of South Sumatra from April to August 2014. This study used split plots. Willis and Tanggamus varieties were main plots, application time (0, 0 and 4 MST) were on subplot, and fertilizer dose (0, 36, 72, 108 kg P2O5 ha-1) was on sub-sub plot. Experiment results showed that soybean productivity in peaty mineral soil was lower than mineral soil. In peaty mineral soil, the application time of phosphorus at 0 and 4 MST was able to increase growth and productivity of soybean, while phosphorus application time on mineral soils was better at 0 and 4 MST of planting time on mineral soils. The dose of 108 kg P2O5 ha-1 increased the productivity of soybean in peaty mineral soils, while a dose of 72 kg P2O5 ha-1 was better in mineral soil. In peaty mineral soil, interaction (Tanggamus, application at 0 and 4 MST as well as 72 kg P2O5 ha-1), showed the highest productivity of soybean (2.83 ton ha-1). Meanwhile, interaction (Tanggamus, application at 0 and 4 MST as well as 72 kg P2O5 ha-1) showed the highest productivity of soybean (3.8 ton ha-1), respectively in mineral soil under saturated soil culture techniques in tidal land. Keywords: Dose of fertilizer, Glycine max (L) Merr., phosphorus, soil acidity, variety